If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5(2x + y) = 0 3x + (2x * 5 + y * 5) = 0 3x + (10x + 5y) = 0 Combine like terms: 3x + 10x = 13x 13x + 5y = 0 Solving 13x + 5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5y' to each side of the equation. 13x + 5y + -5y = 0 + -5y Combine like terms: 5y + -5y = 0 13x + 0 = 0 + -5y 13x = 0 + -5y Remove the zero: 13x = -5y Divide each side by '13'. x = -0.3846153846y Simplifying x = -0.3846153846y
| F(a)=10x-2 | | 8.1+x=3.6 | | 12(x-6)=-8-4 | | 37+2g=87 | | 4-n=4(n-1) | | 4(3x+1)=5x-6 | | -5(1-4m)=6m+37 | | 180=5x+12+6x-10 | | -7p+5p=-3p-31 | | 70-30=10+ | | 4x-12+5x=-30 | | 4x^3-4x^2-224x=0 | | 50-40=10+ | | -3v-3=-21 | | 30x+5(2x+y)=0 | | 7x=11+38 | | y=1.75x-1 | | 23-19=135 | | 12m+5=281 | | 7=-2-3n | | 22+8n=54 | | 20+7-4(x+1)= | | 2+7a+7=20+2a | | 10+3h=-6+2h | | -15x^2=12x-5 | | 3a+3b+2a= | | -17=a-3 | | 12x-12=8+6+6x | | m+4=6m-2 | | 2(2x+4)/2= | | -2=1+x | | 65X=31 |